Preeclampsia Biomarkers - The quest goes on - Kaur, Brinderjeet; Sareen, Rateesh (Journal of Medicine and Health Sciences Research, 2019)
Preeclampsia (PE) is a multisystem disorder of pregnancy and a major cause of maternal morbidity and mortality worldwide. The disease is recently attributed to maternal endothelial dysfunction. The quest for ideal biomarker goes on. Pregnancy-associated plasma protein A (PAPP-A), Placental growth Factor (PLGF) and sFlt-1 (soluble fms-like tyrosine kinase-1) are the new biomarkers that hold promise for future. We present a short review on current biomarkers that would enable us to diagnose PE timely leading to reduced maternal morbidity and mortality , justifying the saying, ‘ a stitch in time saves nine’.